Market Response to Earnings Surprises Conditional on Reasons for an Auditor Change - HACKENBRACK, KARL E.; HOGAN, CHRIS E. (Contemporary Accounting Research, 2002)
Our interest in this study is the relative informativeness of earnings announcements reported before and after Form 8-K disclosures of the reason for an auditor change. We appeal to several models that predict that the market's response to an earnings surprise is positively related to the perceived precision of the earnings report. We predict that the Form 8-K reason disclosures aid investors in updating their expectations of earnings precision by providing useful information about the financial reporting process that produces the earnings report. For 802 auditor changes from late 1991 through late 1997, the average price response per unit of earnings surprise is lower subsequent to an auditor change for companies that switched for disagreement-related or fee-related reasons and higher for those that switched for service-related reasons. This paper provides further evidence on the effects of differential earnings quality on differences in the returns-earnings relation across companies and over time as well as the efficacy of Form 8-K disclosures of reasons for auditor changes.